2003
DOI: 10.1086/375594
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Bacteriological Characteristics of IMP-Type Metallo-β-Lactamase-Producing Pseudomonas aeruginosa

Abstract: IMP-type metallo-beta-lactamase-producing bacteria have recently emerged worldwide. We conducted a case-control study in which 69 inpatients harboring bla(IMP)-positive Pseudomonas aeruginosa and 247 control subjects with bla(IMP)-negative pathogens were investigated. Prolonged hospitalization, antineoplastic chemotherapy, corticosteroid therapy (P=.001), and indwelling urinary catheters (P=.04) were risk factors for isolation of bla(IMP)-positive pathogens. The predominant source was urine (P=.001). The durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 28 publications
2
75
2
1
Order By: Relevance
“…A case-controlled study from Japan showed that patients infected with MBL-producing P. aeruginosa were more likely to receive multiple antibiotics and, more importantly, that infection-related deaths due to IMP-producing P. aeruginosa were more frequent than deaths caused by bla IMPnegative P. aeruginosa (14). The occurrence of an MBL-positive isolate in a hospital setting poses a therapeutic problem, as well as a serious concern for infection control management.…”
Section: Discussionmentioning
confidence: 99%
“…A case-controlled study from Japan showed that patients infected with MBL-producing P. aeruginosa were more likely to receive multiple antibiotics and, more importantly, that infection-related deaths due to IMP-producing P. aeruginosa were more frequent than deaths caused by bla IMPnegative P. aeruginosa (14). The occurrence of an MBL-positive isolate in a hospital setting poses a therapeutic problem, as well as a serious concern for infection control management.…”
Section: Discussionmentioning
confidence: 99%
“…They spread first in Japan and Korea and more recently in Europe (4,26,27) and the Americas (7,11). Large outbreaks by MBL-producing P. aeruginosa strains have been described in hospitals in Italy, Greece, and Korea (4,14,16,18,20,29), as well as in Latin America, notably, including one caused by a P. aeruginosa strain with an SPM-1 ␤-lactamase in Brazil (7). The SENTRY surveillance program for 1999 to 2002 reported MBLs in P. aeruginosa and/or Acinetobacter spp.…”
Section: Description Of Outbreakmentioning
confidence: 99%
“…A particular concern is that acquired MBL genes are located on integron structures that reside on mobile genetic elements such as plasmids or transposons (23), thus enabling widespread dissemination. Clinical infections with such organisms pose serious therapeutic challenges, with increasing reports of poor patient outcomes and death (5,8,14).…”
mentioning
confidence: 99%